Tissue Engineering and New Treatment Options Originated from Cell-culture - ÖZBİLEN ACAR, Gül (Cerrahpaşa Medical Journal, 2014)
Tissue engineering/regenerative medicine is multydisciplinary area including medicine, biology, and engineering. This scientific revolution aims restoration of tissue and organ structure or function with use of living cells. Human health and quality of the life are tried to improve by cell-based therapies. Apart from these, regenerative medicine has diagnostic applications especially involving drug industry. In this review, we focused on tissue engineering and cell-based therapies, and discussed this scientific progress in the light of world literature.